Protecting and enhancing willingness to communicate with idiodynamic peer-peer strategy sharing. (December 2021) - Ducker, Nathan
Abstract: While a wide range of trait-like and situational willingness to communicate (WTC) factors have been investigated, subsequent pedagogical advice often focuses on teacher-led interventions and does not enable learners themselves to overcome immediate WTC related difficulties. This may be because little is known about how students protect and enhance their own WTC levels. This study, therefore, positions students as peer—peer strategy investigators; learners used idiodynamic methodology to interview a selected peer about strategies they used to protect and enhance their WTC during a classroom discussion. Interviewers shared their WTC-related insights in a follow-up class, providing participants with maximum exposure to the elicited WTC-focused strategies. A key finding was that talk-positive students used a combination of expected behaviours and task-outcome-visualization in combination with 'resetting' meta-cognitive strategies to overcome learning difficulties. Furthermore, students reported three approaches to peer—peer strategy sharing: desire for self-improvement, rapprochement with peers, and personal reassurance . In addition to understanding task completion- and communication-difficulties and learning potential WTC-focused strategy resolutions, some individuals reported a change in mind-set and continued to observe their peers' learning-focused behaviours after the study. Thus, this idiodynamic peer—peer approach may be used for ongoing WTC-focused learner development and improved intra-group dynamics.